2019
DOI: 10.3390/s19245336
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered Smart Insole for Monitoring Human Gait Signals

Abstract: With the rapid development of low-power consumption wireless sensors and wearable electronics, harvesting energy from human motion to enable self-powered sensing is becoming desirable. Herein, a pair of smart insoles integrated with piezoelectric poly(vinylidene fluoride) (PVDF) nanogenerators (NGs) are fabricated to simultaneously harvest energy from human motion and monitor human gait signals. Multi-target magnetron sputtering technology is applied to form the aluminum electrode layers on the surface of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Direct conversion of mechanical energy into electricity offers potential as power source for various systems [28, 7, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Direct conversion of mechanical energy into electricity offers potential as power source for various systems [28, 7, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Wei Wang et al presented self-powered insoles integrated with piezoelectric poly vinylidene fluoride (PVDF) nanogenerators (NGs) and manufactured using 3D flatbed knitwear without seams for monitoring user gait and scavenging the walking energy [ 38 ]. The NGs were made by growing aluminum electrodes on the PVDF film.…”
Section: An Overview Of Smart Insoles For Plantar Pressure Detection and Gait Analysismentioning
confidence: 99%
“… Schematic diagram of the self-powered intelligent insole detailing the fabric’s knitted motif ( a ) and the related prototype ( b ) Adapted from [ 38 ]. …”
Section: Figurementioning
confidence: 99%
“…[ 123 ] As shown in Figure 16 , Wang et al used PVDF transducer as the energy harvester and sensor to simultaneously generate electrical energy and monitor the foot pressure. [ 124 ] By deploying different PVDF sensors on the hindfoot and forefoot, the foot pressure can be collected and analyzed while producing electrical power. Besides powering the pressure sensor, Nour et al demonstrated the feasibility of powering a wireless transmitter and LED display.…”
Section: Possible Self‐powered Applicationsmentioning
confidence: 99%